Exploring the Nutritional and Physiological Benefits of Bee-derived Products: Honey and Pollen as Emerging Functional Foods - Ravneet Kaur; Sonika Sharma; Shikha Mahajan; Sukhpreet Kaur (Archives of Current Research International, 2025)
Honey and bee pollen are nutrient -rich natural products with promising health benefits. This study looked at the physical, chemical, nutritional, and antioxidant properties of multifloral honey and bee pollen to see if they could be used as functional foods. The honey sample had a lot of carbohydrates (83.4%), mostly in the form of fructose (38.74%) and glucose (31.38%). The ratio of fructose to glucose was 1.25. It had a total phenolic content of 51.24 mg GAE/g and a DPPH radical scavenging activity of 39.45%, which means it had moderate antioxidant activity. In contrast, bee pollen had a higher nutrient density, with 21.23% protein, 11.68% fiber, and 252.98 mg GAE/g of total phenolics. It also had a lot of potassium (248.02 mg/100 g), calcium (131.76 mg/100 g), and ascorbic acid (13.40 mg/100 g). The antioxidant capacity of bee pollen was noteworthy, as evidenced by its 4.65 µmol Fe²⁺/g FRAP value and 71.69% DPPH activity. Its functional value was further increased by the presence of unsaturated fatty acids and essential amino acids. These findings reinforce their classification as functional foods and highlights their potential role in disease prevention and health promotion.